Avaliação dos efeitos neurotóxicos de cianotoxinas em cladóceros com ênfase na utilização de um biomarcador bioquímico para sua detecção - Freitas, Emanuela Cristina de (Universidade Federal de São Carlos, 2013)
This thesis aimed to evaluate the use of cholinesterases (ChE) of the cladoceran species Pseudosida ramosa and Daphnia magna as a biochemical biomarker of the presence and effects of anatoxin-a(s) at different levels of biological organization (molecular, individual and population), besides the combined effects of the mixtures of the hepatotoxic (microcystins) and neurotoxic (anatoxin-a(s)) extracts in D. magna. A microplate assay was adapted and optimized for measuring the ChE activity of P. ramosa, in order to produce an assay protocol for this species. The analysis on the performance of ChE assays in P. ramosa showed that these are suitable for the quantifying of enzymatic activity in this species. P. ramosa showed to be an adequate alternative to the exotic cladoceran D. magna. Thus, it was proposed an assay protocol, which it meets the best combination of parameters for the using of ChE activity of P. ramosa as a biochemical biomarker. The ChE activity of P. ramosa and D. magna were specific for the indication of the presence of anatoxin-a(s), since no effect on the enzymatic activity of these species was observed when they were exposed to the microcystins. In the acute exposures (48-h) to the anatoxin-a(s) extract and to the paraoxon-methyl, P. ramosa was more sensitive than D. magna for ChE activity and survival endpoints. Also, P. ramosa was more sensitive than D. magna when exposed to the anatoxin-a(s) extract for 7 days. When the relationships between the ChE inhibition and individual and populational endpoints were evaluated, different responses were observed for the studied species. The ChE inhibition in P. ramosa had a very close relationship with the survival in the acute exposures to the anatoxin-a(s) extract and to the paraoxon-methyl. For D. magna, on the other hand, this relationship was not linear, being high levels of ChE inhibition associated with almost no mortality. The ChE activity in P. ramosa was also a good predictor of the chronic effects of anatoxin-a(s) extract at higher levels of biological organization, since ChE inhibition (48 h) was linearly linked to the sub-lethal effects on the reproduction (21 days) and on the population growth rate (21 days). For D. magna, these relationships could not be established, possibly due to species-specific differences in the affinities of both acetylcholinesterase and pseudocholinesterases to the toxicants. Thus, for the using of ChE as a biochemical biomarker in the risk assessments of neurotoxic cyanobacteria blooms in tropical regions, it is recommended the use of native species, especially of P. ramosa, since the model species D. magna could overestimate the risk to the local species. When the effects of the mixtures of the hepatotoxic and neurotoxic extracts were evaluated on the survival and feeding rates of D. magna, additive and synergistic responses were only observed on the feeding rates. Therefore, since different types of cyanotoxins are found in the natural environments in combination, the risks of these toxins on the zooplanktonic community should be evaluated not only individually, but also as mixtures.
Keywords: Meio ambiente de água doce; Anatoxina-a(s); Microcistina; Colinesterases; Misturas complexas; Ecotoxicologia tropical; Paraoxon-metil; Biomarcador bioquímico; Pseudosida ramosa; Daphnia magna; Anatoxin-a(s); Microcystins; Paraoxon-methyl; Biochemical biomarker; Cholinesterases; Complex mixtures; CIENCIAS BIOLOGICAS::ECOLOGIA